Answer:
B. -1
Explanation:
If we have a parabola whose equation is:
![y=ax^(2) +bx+c](https://img.qammunity.org/2021/formulas/mathematics/middle-school/px9qcbnlyt1idjui2aqccn4ae57yf9xiku.png)
The line of symmetry is calculated as:
![x=(-b)/(2a)](https://img.qammunity.org/2021/formulas/mathematics/high-school/lx9c5kktl1ahcls2nih0ev6ihpvxaw3728.png)
Now, we have the equation
and the line of symmetry is
![x=-2](https://img.qammunity.org/2021/formulas/mathematics/high-school/x874kw28hwnpm2t0ubt6p66qgmkx3rahvb.png)
Where:
![b=-4\\c=3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/whxzjefgl3f433v2s58y11ln4vemr199aa.png)
So, we can replace
by -4 and
by -2 and solve for
using the following equation as:
![x=(-b)/(2a)\\-2=(-(-4))/(2a)\\-2(2)a=4\\-4a=4\\a=-1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/le91p0mc6oktjhmyw1bh2fnp17ps1bi8l1.png)
It means that the equation of the parabola is equal to:
![y=-1x^(2)-4x+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1bkk06v70vsi1aoggqjlln4m79nixpoug5.png)